2015
DOI: 10.3390/nu7064199
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Cycling Across Soil-Plant-Atmosphere Interfaces: A Critical Review

Abstract: Selenium (Se) is an essential element for humans and animals, which occurs ubiquitously in the environment. It is present in trace amounts in both organic and inorganic forms in marine and freshwater systems, soils, biomass and in the atmosphere. Low Se levels in certain terrestrial environments have resulted in Se deficiency in humans, while elevated Se levels in waters and soils can be toxic and result in the death of aquatic wildlife and other animals. Human dietary Se intake is largely governed by Se conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
279
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(296 citation statements)
references
References 283 publications
4
279
0
1
Order By: Relevance
“…Foliar application of Se is better and efficient means of Se-biofortification than application of Se fertilizers in soil, due to avoidance of root to shoot translocation of Se (Winkel et al, 2015). Use of Se fertilizers in soil have low rates of Se enrichment in edible part of plant, moreover, long term use can be toxic to nearby ecosystem, hence use of Se fertilizers should be done carefully to avoid toxic aspects (Winkel et al, 2015).…”
Section: Selenium Biofortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Foliar application of Se is better and efficient means of Se-biofortification than application of Se fertilizers in soil, due to avoidance of root to shoot translocation of Se (Winkel et al, 2015). Use of Se fertilizers in soil have low rates of Se enrichment in edible part of plant, moreover, long term use can be toxic to nearby ecosystem, hence use of Se fertilizers should be done carefully to avoid toxic aspects (Winkel et al, 2015).…”
Section: Selenium Biofortificationmentioning
confidence: 99%
“…Use of Se fertilizers in soil have low rates of Se enrichment in edible part of plant, moreover, long term use can be toxic to nearby ecosystem, hence use of Se fertilizers should be done carefully to avoid toxic aspects (Winkel et al, 2015). In Finland and New Zealand, use of inorganic Se fertilizers is a common practice to increase Se content in agricultural products (Schiavon et al, 2013; Wang Y. D. et al, 2013).…”
Section: Selenium Biofortificationmentioning
confidence: 99%
“…An important factor influencing the isotopic behavior of selenium in soils appears to be the abundance of organic matter and other reductants that re-reduce selenium oxyanions deeper in the soil profile (Zhu et al 2014;Schilling et al 2015). This and other processes further affect selenium uptake into plants (Winkel et al 2015).…”
Section: Reservoirs At the Earth's Surfacementioning
confidence: 99%
“…However, it has also been suggested that nonenzymatic reduction by reduced Winkel et al ( 2015 ) and Pilon-Smits ( 2015 )) 6 Selenium and its Role in Higher Plants 260 glutathione (GSH) may play a signifi cant role in selenite reduction (Terry et al 2000 ). Se 2− can subsequently be coupled to O-acetylserine (OAS) to form SeCys, by means of OAS thiol lyase (also called cysteine synthase).…”
Section: Plant Selenium Metabolismmentioning
confidence: 99%
“…As well known, weathering of rocks is the major source of environmental Se and in general, limestone and sandstone contain lower concentrations of Se (<0.1 mg kg −1 ), whereas, as reviewed by Wu ( 2004 ), shale tend to contain higher Se concentrations (0.6 mg kg −1 ). The biogeochemistry of Se is characterized by several reviews (e.g., Hartikainen 2005 ;Di Gregorio 2008 ;Fordyce 2013 ;El-Ramady et al 2014 ;Sharma et al 2015 ;Nancharaiah and Lens 2015 ;El-Ramady et al 2015a ;Gojkovic et al 2015 ;Winkel et al 2015 ). These biogeochemical processes have many distinct features including (1) the substitution of Se for S decreases if the oxygen fugacity increases; (2) the stable SeO 4 2− are rapidly oxidized in surface conditions; (3) the adsorption of SeO 4 2− on soil minerals is nearly quantitative (Wang and Gao 2001 ).…”
Section: Biogeochemistry Of Seleniummentioning
confidence: 99%